1959
DOI: 10.1161/01.res.7.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Reactions due to Plasma Incompatibility in Dogs

Abstract: Plasma incompatibility was investigated as a possible factor in transfusion reactions in dogs. Urticaria, failure to retain within the circulation the equivalent of transfused plasma volume and protein, and increased gastric acid secretion almost invariably followed transfusion of plasma from another dog but not transfusion of the dog's own plasma. The cutaneous reactions were abolished and the retention of plasma was improved by administration of an antihistamine. Erythroeyte isoagglutinins did not appear to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1960
1960
1968
1968

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In the present experiments dextran was infused to maintain blood volume, cardiac output and therefore tissue perfusion. Plasma or blood from donor animals was not used because of reports of incompatibility of blood and idiosyncratic responses to dog plasma (Bliss, Johns & Burgen, 1959;Remington & Baker, 1959). In addition, to prevent anoxia and its effects on chemoreceptor discharge as well as its effect on the metabolic acidosis these dogs were respired with oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiments dextran was infused to maintain blood volume, cardiac output and therefore tissue perfusion. Plasma or blood from donor animals was not used because of reports of incompatibility of blood and idiosyncratic responses to dog plasma (Bliss, Johns & Burgen, 1959;Remington & Baker, 1959). In addition, to prevent anoxia and its effects on chemoreceptor discharge as well as its effect on the metabolic acidosis these dogs were respired with oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…These were first demonstrated in dogs by Bliss, Johns, and Burgen (1959), who found that non-autologous plasma caused cutaneous and other reactions, as well as being an inferior expander of the circulation as compared with autologous plasma. Similar findings were described by Remington and Baker (1959).…”
Section: Discussionmentioning
confidence: 99%
“…However, naturally occurring iso-antibodies appear to be very uncommon, and it is exceedingly unlikely that they could account for the reactions that were detected in over half of the subjects receiving non-autologous infusions. It must be admitted, however, that the considerable number of platelets in the infused plasma may leave a residual doubt about whether they can be entirely excluded from involvement in the reactions, but in similar experiments in the dog comparable reactions to non-autologous plasma transfusions have been found (Bliss et al, 1959) even though the administered plasma had been Seitz-filtered to ensure that all cells had been removed. In this case we can exclude the participation of whole platelets in the reaction, although one cannot exclude the presence of soluble products of platelet breakdown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain more quantitative information requires skilled cross-matching of blood or red cells, the use of fresh blood, and the avoidance of allergic and other reactions. These requirements are rarely fully met in animal experiments, which renders interpretation difficult (239). In man or animals exposed to high altitude such problems are avoided.…”
Section: Interactions Between Red Cell and Plasma Volumementioning
confidence: 99%